Energetics of the lower tropospheric eddies in wave number domain during northern summer monsoon (MAUSAM, 2000)
Lower tropospheric energetics and energy processes of zonal waves for three consecutive northern summer monsoon seasons of 1994, 1995 and 1996 are presented. Fourier technique is used. The features of the tropical and extra-tropical regions are very well reflected by the data set used for this study. The results do not show marked year to year variations in the pattern of energy processes. The character of energy processes differs significantly from one latitudinal region to other. Wave to zonal mean flow interactions and wave to wave interactions are almost opposite in character over R1 (10° S -10° N) and R2 (10° N -30° N). L (n) interaction indicates that R1 acts as source of kinetic energy to the waves over R2. Particularly, standing waves I and 2 over RI are the major source of kinetic energy to the waves over R2. Extra-tropical region R3 (30° N -50° N) is dominated by transient waves while tropical regions R1 and R2 are dominated by standing waves. Medium and short waves have significant contributions over extra-tropical region whereas tropical regions are dominated by long waves. The pattern of energy processes over R3 is somewhat similar to the energy processes over R1. This is because both the regions have anti-cyclonic lateral shear.